Cancer Prevention with Molecular Target Therapies - Paleari, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Personalized medicine plays an important role in cancer prevention. To date, it is clear that many cancers are molecularly distinct subtypes, and different therapeutic approaches would be required for each. Indeed, the identification of cancer susceptibility genes permits identifying patients "at risk" of developing neoplasia and supports modifying individual risk behaviors or the choice of preventive therapy. Additionally, the efficacy of various targeted therapies in different cancer subtypes suggests that treatment choices in the near future will be more and more centered on molecular signatures. Data from preclinical, clinical, and observational studies have revealed the ability to prevent cancer development for compounds with different indications than cancer. The concept of drug repurposing permits combinations that can target several critical pathways of a specific disease, decreasing the risk of resistance observed when using single-agent targeted therapy.This open-access Special Issue brings together original research and review articles on molecular oncology with attention to the early detection and prevention of cancer. It highlights new findings, methods, and technical advances in molecular cancer research. The main feature of this Special Issue is to provide an open-source sharing of significant works in the field of molecular oncology that can increase our understanding of cancer development, which may lead to the discovery of new molecular diagnostic technologies and targeted therapeutics.